Link adaptation based on video quality monitoring for H.264/AVC video transmission over WLANs - Abdul Rahman, Farah Diyana; Agrafiotis, Dimitris (IEEE, 2016)
Link adaptation algorithms employed by wireless routers traditionally use retransmission to achieve high error-free data throughput. Such methods do not take into account the delay sensitive nature of video data. In this paper, we investigate the use of reduced-reference video quality monitoring for video oriented link adaptation. Estimation of the quality degradation due to channel errors is performed at the receiver side using the NoReference video quality Monitoring metric. The estimates are sent to the encoder side where, combined with mean squared error values for the encoded video, they form a reduced reference metric that gives information about the quality of the video at the receiver. Link adaptation is then performed using this reduced reference metric.